2005
DOI: 10.1099/jmm.0.46069-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of dental caries incidence associated with Streptococcus mutans and Streptococcus sobrinus in pre-school children

Abstract: Streptococcus mutans and Streptococcus sobrinus are known to be associated with the development of dental caries. In this study these bacteria were detected in pre-school children (each with primary dentition, age range 3-5 years, n ¼ 60) using a PCR method, and then their presence was compared with the incidence of dental caries over a 1-year period. Plaque samples were collected from all erupted tooth sites using a sterile toothbrush. Dental examinations at the beginning of the study (baseline) and after 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 32 publications
11
92
4
3
Order By: Relevance
“…However, the outcomes of the present study were quite different from those of Okada et al (16), who reported 72.8% and 61.1% for S. mutans and S. sobrinus in 3-5 years old Japanese preschool children. In another study, Okada et al (17) found prevalences of 61.7% and 56.6% for S. mutans and S. sobrinus, respectively, in Japanese children. In both studies (16,17) the authors reinforced the statement that children who harbor both bacteria together have a significantly higher caries incidence and incremented increase, compared to those with S. mutans alone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the outcomes of the present study were quite different from those of Okada et al (16), who reported 72.8% and 61.1% for S. mutans and S. sobrinus in 3-5 years old Japanese preschool children. In another study, Okada et al (17) found prevalences of 61.7% and 56.6% for S. mutans and S. sobrinus, respectively, in Japanese children. In both studies (16,17) the authors reinforced the statement that children who harbor both bacteria together have a significantly higher caries incidence and incremented increase, compared to those with S. mutans alone.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Okada et al (17) found prevalences of 61.7% and 56.6% for S. mutans and S. sobrinus, respectively, in Japanese children. In both studies (16,17) the authors reinforced the statement that children who harbor both bacteria together have a significantly higher caries incidence and incremented increase, compared to those with S. mutans alone. In the present study, it was no detected the presence of both species together in any dental plaque sample from Brazilian children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the complex interspecies interactions, there is also evidence to suggest that other species of oral streptococci may have different roles in the caries process (Kanasi et al, 2010). Most previous studies on the microbial risk indicators for dental caries have focused mainly on one or several possible pathogens Ge et al, 2008;Okada et al, 2005). Studies that have investigated dental plaque from a microbial ecological perspective are rare.…”
Section: Oral Streptococci Succession Associated With S-eccmentioning
confidence: 98%